Analisis Beberapa Faktor Yang Mempengaruhi Penanaman Modal Asing Pada Industri Manufaktur Di Jawa Timur - Suwarno, Suwarno (Jurnal Riset Ekonomi dan Bisnis, 2008)
The foreign investor into East Java is expected to fulfill the requirement of capital as well as the incentive in defraying development besides cultivation of domestic capital in production process especially in industrial sector of manufacture. Reason selecting of foreign investment at industry of manufacture become research object because foreign investment at industry of manufacture natural growth is fluctuative. This research aims to identify the influence of Amount of Industry, Domestic Product of Regional Bruto, Foreign Currency Rate, and Inflation to Foreign Investment. Secondary data is used and is taken in range time of 15 years. Doubled linear regression Analysis is used to analyze the research’s data. Result of doubled linier regression analysis indicated that the amount of industry of manufacture, domestic product bruto regional, foreign currency rate and inflation have an effect on foreign investment at industry of manufacture simultaneously. While result which is examined by partial variable amount of industry of manufacture domestic product and regional bruto does not have influence which significant to foreign investment at industry of manufacture, result of examination by partial foreign currency rate variable and inflation have influence which is significant to foreign investment at industry of manufacture.Keywords: Industry, Domestic Product of Regional Bruto, Foreign Currency Rate, Inflation, Foreign Investment